#TITLE_ALTERNATIVE# - ARINITA (NIM 15107022); Pembimbing: Dr. Deni Suwardhi, ST. MT., dan Dr. Ir. Tatacipta Dirgan, DIANDRA
Reverse Engineering is a systematic evaluation of a product which involves direct or indirect copies to realize the function or performance of an object, purpose of replication, or adding improvement to the existing object. Reverse engineering can be viewed as the process of analyzing a system to: identify the system's components and their interrelationships, create representations of the system in another form or a higher level of abstraction, and to create the physical representation of that system. The reverse-engineering process involves measuring an object and then reconstructing it as a 3D model. Many methods can be used to measure an object, in this case the method used was Close Range Photogrammetry and Laser Scanning. Both provide data called point clouds that represent the objectÃ‚Â’s surface. Point clouds are the basic data to make 3D model, representing the geometry of the part in terms of surface points as the first step in creating parametric surface patches. A good polymesh is created from the point cloud using reverse engineering software. The cleaned-up polymesh, or NURBS surfaces are exported to CAD packages for further refinement, analysis, integration. Finally produces the physical object using final model. and then remodeling again with photogrammetry method to get a new three dimensional model to then be compared with the first final model.